Process model for a software testing service and its influence on final product quality (Innovation & Development in Engineering and Applied Science, 2026)
The research aimed to determine how a process model for software testing services affects the quality of the final product. This study is justified by the lack of a unified approach that integrates frameworks such as CMMI, TMMI, ITIL, and PMBOK to manage testing services under outsourcing schemes. A Design Science methodological approach was applied, combining literature review, model development, and validation through a case study in a Peruvian specialized consultancy. The results showed substantial improvements in delivery time efficiency, reduction of incidents, and increased customer satisfaction. Implementing the model enabled more rigorous process control, demonstrating that adopting international best practices has a positive impact on the quality and reliability of the delivered software. The study concludes that the proposal contributes to standardizing critical processes in testing organizations.